PENGGUNAAN MEDIA BELAJAR SMARTPHONE PADA SISWA DI SMA NEGERI 2 MANADO - Meilita Prisilia Maun; Maryam Lamadirisi; Y.D.A. Santie (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2020)
The research objective was to identify and describe the use of smartphone media in the teaching and learning process of students at SMA N 2 Manado. The problem in research is how to use smartphone learning media. This research uses qualitative methods with techniques such as observation and interviews. Unstructured interviews are independent interviews where the researcher does not use interview guidelines that have been arranged systematically and completely for data collection Sugiyono (2011: 233). The results of research in the field show that the use of smartphones as a medium of learning in learning activities greatly helps educators and students in finding references to teaching materials on google, chrome, browser, widely easily and in a short time. One of the media favored by students today is smartphones so that with the help of a smartphone it can increase students' motivation to learn.